Socialization Training Programs Physical Condition Of The Athletes In The Face Of The Situation Of The Pandemic And Post Pandemic In KONI Kota Payakumbuh Sumatera Barat - Yendrizal Yendrizal; Ronni Yenes; Erizal N (Jurnal Humanities Pengabdian Kepada Masyarakat, 2020)
Based on studies in the field, found the problem that almost all of the coaches of the sport in the KONI Kota Payakumbuh have constraints in the preparation of training programs physical condition to the athlete in a situation of pandemic COVID-19 right now. It is originated from the low understanding of the trainers about the basic concepts of the physical conditions in sports coaching achievement for athletes. Through this community service activity of the team of community services Universitas Negeri Padang will give you a full u in scientific to the participants about: (a) the basic concept of training the physical conditions in sports coaching achievements against the athlete. (b) basic Concepts related to test and measurement of the physical condition of the athlete. (c) the Design and preparation of training programs physical conditions in the face of the situation of the pandemic and post-pandemic which according to The rules of the science of Sports Coaching (d) Innovation forms of exercise physical conditions with the intensity adjusted to each branch of the sport. The delivery of material to the participants was performed through the stages of presentation, discussion, practice with mentoring, and evaluation. The results of the activities of the participants obtained is: (a) Have an understanding of the basic concepts of training the physical conditions in sports coaching achievements. (b) Have an understanding and be able to perform the test, measurement, and evaluation of the physical condition of the athlete. (c) is Capable of designing training programs physical conditions in the face of the situation of the pandemic and post-pandemic. (d) able to innovate in compiling forms of exercise physical conditions with the intensity adjusted to each branch of the sport.